Weather risk: How does it change the yield benefits of nitrogen fertilizer and improved maize varieties in sub‐Saharan Africa? - Hurley, Terrance; Koo, Jawoo; Tesfaye, Kindie (Wiley, 2018)
The purpose of this research was to explore how weather risk affects the value of nitrogen fertilizer use and improved seed variety adoption to sub‐Saharan African (SSA) maize farmers. It contributes to the literature by providing additional broad support for the hypothesis that low rates of fertilizer use and improved seed variety adoption can be attributed to the fact that the SSA landscape is heterogeneous, so fertilizer and improved seed are not always advantageous, especially when considering the potentially high cost to farmers of obtaining fertilizer and improved seed. The analysis finds a synergy between nitrogen fertilizer and improved seed varieties. While the benefits of nitrogen tend to increase overtime without improved seed varieties and the benefits of improved seed varieties tend to decrease overtime without nitrogen, combining the two provides more sustained productivity benefits. Therefore, securing both nitrogen use and improved seed variety adoption is important for promoting sustained maize productivity increases across much of SSA. The research also contributes to the literature by using a methodology for calculating willingness to pay bounds that assess the importance of farmers’ risk tolerances as a barrier to fertilizer use or improved seed variety adoption.